Izgradnja povjerenja kao ključni faktor unapređenja odnosa između liječnika i pacijenta / Building Trust as a Key Factor of Improving Doctor-Patient Relationship - Spahić, Aida (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
Taking into consideration the relevant literature that deals with doctor-patient relationship, modern conditions of life and work of medical proffesionals, the growing public interest in the implementation of Law on patients' rights, as evidenced by numerous articles in the electronic media, this article is aimed on exploring the basic obstacles for improving this relationship and offer guidelines for action both at institutional, and individual levels. It analyzes the different models of doctor-patient relationship, the main challenges of this relationship in light of the information technology, health care organization and education programs of medical profile, taking into account the Bosnian context. Conclusion emphasises that communication skills and an appropriate level of professionalism are built not only on many years of medical practice but earlier in the educational process itself. The outcome of treatment largely depends on building an appropriate level of trust between doctor and patient. The guidelines for action must be focused on strengthening the moral dimension of the medical profession and restore its integrity in the eyes of public, by restoring confidence, the doctor-patient relationship is based on.